ANALYSIS OF FACTORS AFFECTING THE PERFORMANCE OF INDONESIA PEACEKEEPING CONTINGENT AT UNITED NATIONS MISSION - Susilo Adi Purwantoro; Hamidah; Agung Wahyu Handaru (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The purpose of this study is to investigate the moderating role of organization behavior citizenship in the influence of leadership, training effectiveness and teamwork on soldier performance in the context of Indonesia peacekeeping contingent at United nations mission. The study surveyed 319 soldiers by distributing questionnaire among total population of 1,566 enlisted soldiers. The statistical data are tested by Lisrel application. The study found that leadership, training effectiveness, teamwork directly had an influence on the performance of soldiers. Likewise, when the three factors through the moderating variable Organization Behavior Citizenship (OCB), it is produced that these three factors significantly influence the performance of soldiers who participate in the UN Peacekeeping Operation. To enhance the performance of soldiers, the unit has to build the leadership, train the member effectively and build the teamwork. It also has to create the OCB environment to increase the effect of those variables. To our best knowledge, it is the first research which studies the moderating role of OCB on relationship between leadership, training effectiveness, teamwork on soldier performance